Analisis Kedekatan Hubungan antar Genotipe Pepaya Berdasarkan Karakter Morfologi dan Buah - Ketty Suketi; Roedhy Poerwanto; Sriani Sujiprihati; , Sobir; Winarso D. Widodo (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2010)
<!-- /* Font Definitions */ @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:Calibri; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:IN; mso-no-proof:yes;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> A study was conducted to determine the variation and relationships among papaya genotypes based on morphological and fruit characteristics in order to produce high quality papaya fruits. Fruit characterization study is very useful for genotype improvement and genotype classiﬁ cation of papaya. In this study the morphological characters of 36 genotypes were analyzed to determine their phenotypic variabilities. The relationships between genotypes based on all of the morphological and fruit characteristics were tested by subjecting the data to multivariate principal component analysis and to cluster analysis. Based on the dendrogram generated from vegetative and generative characters, the 36 genotypes could be grouped into 11 clusters on a threshold of 1.6 and formed 6 clusters on a threshold of 1.8. The dendrogram was able to explain the close relationship between IPB 5 x IPB 1 and IPB 5 x IPB 4, IPB 2 and IPB 7, IPB 1 and IPB 3 genotype. The scattered diagram of generative variable divided the papaya genotypes into three groups based on fruit sizes i.e small group (IPB 1, IPB 3, IPB 4, IPB 3 x IPB 4, IPB 1 x IPB 9), medium group (IPB 5, IPB 7, IPB 8, IPB 9) and big group (IPB 2, IPB 10). The IPB 1, IPB 3 and IPB 4 were different from IPB 2 in fruit shapes, petal length of male ﬂ owers, inﬂ orescence size and fruit length. The hybrid plants obtained from crossings with IPB 10 were different from the other genotypes in the colours of female-, hermaphrodite-, and male ﬂ ower-lobes. Subsequently the scatter diagrams also revealed that several genotypes i.e. IPB 2 x IPB 6, IPB 1 x IPB 5, IPB 1 x IPB 9, IPB 5 x IPB 1 and IPB 5 x IPB 2 had superior characters ideotype similar to IPB 1, IPB 3 and IPB 8 genotypes. Keywords: Carica papaya, hermaphrodite, female, dendrogram, scatter diagram, ideotype